2021
DOI: 10.1021/acs.chemmater.1c02371
|View full text |Cite
|
Sign up to set email alerts
|

High-Tc Superconducting Hydrides Formed by LaH24 and YH24 Cage Structures as Basic Blocks

Abstract: Based on recent studies regarding high-temperature (high-T c) La–Y ternary hydrides (e.g., P1̅-La2YH12, Pm3̅m-LaYH12, and Pm3̅m-(La,Y)­H10 with a maximum T c ∼ 253 K), we examined the phase and structural stabilities of the (LaH6)­(YH6) y series as high-T c ternary hydride compositions using a genetic algorithm and ab initio calculations. Our evaluation showed that Pm3̅m-LaYH12 reported in the previous study was unstable during decomposition into R3̅c-LaH6 + Im3̅m-YH6. We also discovered new crystal structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…For ternary cases, a very recent experiment on the La–Y–H system has revealed that the synthesized (La,Y)­H 10 at P = 180 GPa exhibits a T c of 253 K . More interestingly, the pressure required for (La,Y)­H 10 to achieve superconductivity is lower than that of the LaH 10 high-temperature superconductor, indicating that the ternary hydride has more potential in the search for low-pressure room-temperature superconductivity. , The stability analysis and superconductivity prediction for a minor portion of ternary metal hydrides, such as La–Y–H, Ca–Y–H, Sc–Ca–H, Sc–Y–H, Y–Mg–H, and Ca–Mg–H, have been accomplished recently by theoretical calculations. The majority of the high-temperature (high- T c ) superconducting compounds in the aforementioned systems prefer the cage-like structures. For example, -CaYH 12 with cubic structure preserves the clathrate structure consisting of the H 24 cages, as does CaH 6 and YH 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For ternary cases, a very recent experiment on the La–Y–H system has revealed that the synthesized (La,Y)­H 10 at P = 180 GPa exhibits a T c of 253 K . More interestingly, the pressure required for (La,Y)­H 10 to achieve superconductivity is lower than that of the LaH 10 high-temperature superconductor, indicating that the ternary hydride has more potential in the search for low-pressure room-temperature superconductivity. , The stability analysis and superconductivity prediction for a minor portion of ternary metal hydrides, such as La–Y–H, Ca–Y–H, Sc–Ca–H, Sc–Y–H, Y–Mg–H, and Ca–Mg–H, have been accomplished recently by theoretical calculations. The majority of the high-temperature (high- T c ) superconducting compounds in the aforementioned systems prefer the cage-like structures. For example, -CaYH 12 with cubic structure preserves the clathrate structure consisting of the H 24 cages, as does CaH 6 and YH 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several possibly stable structures were generated based on the stoichiometric composition (YH 6 ) x (EuH 6 ) y as displayed in the convex-hull diagram in Figure 1, among which Cmmm-YEu 3 H 24 , Cmmm-YEuH 12 , Immm-YEu 3 H 24 , and F m 3m-Y 3 EuH 24 seemed to be thermodynamically stable. The existence of promising high-T c ternary hydride candidates based on binary hexahydrides have already been investigated for La-Ce-H [34], Ca-Y-H [31,56], La-Y-H [35], Y/La-K-H [57]. Nevertheless, all the other compositions lying above the convex-hull are meta-stable structures which could potentially decompose into their parent binaries Im 3m-YH 6 and Im 3m-EuH 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies [35,57] employing machine learning technique indicate towards the stability dependence on the relative admixture of the two binaries taking part in the formation of the ternary phase. In Figure 1, our predicted ternary phases (EuH 6 ) x (YH 6 ) y show the instability along x-axis as pressure gets higher and higher consistent with the preceding works.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But then multi-component hydrides contain more combinations of elements, they are more promising in the search for high(room)-temperature superconductivity. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] For example, magnesium hydride can dissociate the H 2 molecule into atomic H by lithium doping, thus increasing its electron concentration at the Fermi level (E F ), enabling it to reach a T c value of 473 K at 250 GPa. [47] Furthermore, recent research has revealed that a small amount of carbon doping in H 3 S can result in room superconductivity (T c = 287.7 ± 1.2 K at 267 ± 10 GPa).…”
Section: Introductionmentioning
confidence: 99%